Mothers' Perceptions of Labor Support. Issue 6 (November 2015) - Unknown
Abstract: Purpose: The purpose of this study was to describe mothers' perceptions of labor support during childbirth. Study Design and Methods: A cross-sectional, descriptive, correlational survey design was used. Data were collected using the Bryanton Adaptation of Nursing Support in Labor Questionnaire (BANSILQ) completed by new mothers ( n = 260) in the postnatal ward in a Finnish university hospital. Nonparametric methods were used for data analysis. Results: Mothers perceived emotional assistance to be most important. From the list of midwives' labor support behaviors provided in the survey, the following were considered most helpful: giving praise, treating on an individual basis, and answering questions truthfully and understandably. Clinical Implications: Emotional, tangible, and informational labor support enhanced the mothers' birth experiences. Labor support should be provided when caring for every mother during childbirth. An evidence-based model of labor support should be used for nursing and midwifery education and clinical practice. Abstract : This study of new mothers offers valuable information for those who care for women during labor and birth. New mothers really appreciated labor support and valued emotional support above other types of support. Giving praise was identified as one of the most important aspects of helping a woman cope with the process of labor.